2017
DOI: 10.1038/s41598-017-00245-1
|View full text |Cite
|
Sign up to set email alerts
|

Energy use and carbon footprints differ dramatically for diverse wastewater-derived carbonaceous substrates: An integrated exploration of biokinetics and life-cycle assessment

Abstract: Energy neutrality and reduction of carbon emissions are significant challenges to the enhanced sustainability of wastewater treatment plants (WWTPs). Harvesting energy from wastewater carbonaceous substrates can offset energy demands and enable net power generation; yet, there is limited research about how carbonaceous substrates influence energy and carbon implications of WWTPs with integrated energy recovery at systems-level. Consequently, this research uses biokinetics modelling and life cycle assessment ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Hence, the way forward in this research is to explore nature-based and hybrid treatment systems wastewater treatment systems 61 . This includes integration of energy recovery through biological pathways, and utilisation of green chemicals that could improve yields and decrease energy consumption 62 , 63 . Furthermore, nature-based solutions combined with scaled decentralization may be better suited for developing countries such as Philippines than chemical-based resource recovery 64 .…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the way forward in this research is to explore nature-based and hybrid treatment systems wastewater treatment systems 61 . This includes integration of energy recovery through biological pathways, and utilisation of green chemicals that could improve yields and decrease energy consumption 62 , 63 . Furthermore, nature-based solutions combined with scaled decentralization may be better suited for developing countries such as Philippines than chemical-based resource recovery 64 .…”
Section: Resultsmentioning
confidence: 99%
“…This is primarily due to the difference in the influent quality of industrial and municipal wastewater. Previous studies have reported that the GHG emission intensity of municipal WWTPs varies with wastewater influent quality in the range of 0.1–2.4 kg CO 2 -eq m −3 [ 49 , 50 ]. For municipal WWTPs, the ratio of biodegradable COD to TN is a significant parameter that affects the GHG emissions in the wastewater biological treatment process as direct GHG emissions have been shown to increase from 0.49 to 0.63 CO 2 -eq m −3 with a decreasing COD/TN ratio [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, they indicated that under regular operation, a conventional wastewater treatment facility is estimated to consume 631.24 kWh of electricity from the grid per year and per 1 PE (person-equivalent), with a corresponding carbon footprint of 1.16240 kg CO 2 -eq/PE (Zawartka et al, 2020). When expressed under the functional unit of one cubic meter of treated wastewater, reported carbon footprint values may range from 0.1 to 2.4 kg CO 2 -eq (Li et al, 2017b;Maktabifard et al, 2020;Wang et al, 2016a). Similarly, a recent study by Maktabifard et al (2020) investigated the carbon footprint of six full-scale wastewater treatment plants, and for those plants fully dependent on the power grid, indirect emissions due to energy consumption accounted for approximately 69-72% of the entire carbon footprint (Maktabifard et al, 2020).…”
Section: Other Radicalsmentioning
confidence: 99%